Prognostic significance of Fc receptor-like 1 in patients with chronic lymphocytic leukemia, hairy cell leukemia, and various B-cell non-Hodgkin's lymphoma. (2019) - Yousefi, Zahra; Eskandari, Nahid
Abstract: Fc receptor-like 1 (FCRL1) positively regulates B-cell responses and may involve in the pathogenesis of B-cell malignancies. This study examined the expression pattern of FCRL1 in B-cell non-Hodgkin's lymphoma patients using real-time PCR and flow cytometry. The results revealed higher levels of FCRL1 expression in diffuse large B-cell lymphoma, hairy cell leukemia, and Burkitt lymphoma patients compared with control groups. There was a significant reduction in the levels of FCRL1 expression in chronic lymphocytic leukemia and mantle cell lymphoma patients compared with healthy individuals. These findings suggest FCRL1 as an excellent marker for the prognosis or immunotherapy of B-cell malignancies.